LITERACY ADVENTURE: BUILDING A LOVE OF READING FROMAN EARLY AGE GAMPONG PULO KITON KABUPATEN BIREUEN: PETUALANGAN LITERASI: MEMBANGUN CINTA MEMBACA SEJAK DINI GAMPONG PULO KITON KABUPATEN BIREUEN - Andriani, Dela; Fidyati; Deni; Eri Saputra (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The tri dharma of higher education is an obligation imposed on academic lecturers, comprising elements of teaching, research, service, and support. The Literacy Adventure Activity: Building a Love ofReading from an Early Age is a community service initiative that aims to foster a love of reading inchildren in Pulo Kiton Village, Kota Juang District. This program is designed to enhance early childhoodliteracy through a fun and interactive approach, featuring storytelling activities, educational games, and exploration of storybooks. This activity involves the active participation of the local community,especially parents and village officials, in creating a literacy environment. Through mentoring, thisactivity also aims to provide moral support and encouragement to children in reading. The results of this activity demonstrate active participation among children, as well as increased awareness among their immediate environment, particularly parents and village officials, about the importance of literacy from an early age. This service contributes to building a culture of literacy in Pulo Kiton Village. It is expected to have a long-term impact on the intellectual and social development of children in the area.